The Influence of Company Profitability and Size on Dividend Policy with Company Value as Moderating Variable - Septiana Mar’atus Sholikhah; Nabila Kharimah Vedy; Zain Khiswari (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2022)
There are many factors that can lead to the perspective of the company's profitability related to dividend policy with company value as a moderating variable. Every investor wants a high return on capital. The ease of investors in investing profitability is an indicator of assessment in seeing the sustainability of the company. Thus, high profitability encourages companies to provide high policies to shareholders. The number of companies engaged in the banking financial sector on the Indonesia Stock Exchange is 45 banking companies. Meanwhile, the sample size of this research is 10 banking companies. The method used in this research is MRA (Moderate Regression Analysis). The results showed that profitability and company size had a positive effect on the company's dividend policy. Next, company value moderates the effect of profitability on dividend policy. However, it does not moderate the effect of company size on company value.